Synchronization of oestrus with PGF2Î± analogue and ear implant and serum oestradiolâ€“17ÃŸ and progesterone profile in Asom local cows - Deka, Ilakshy; Goswami, J; Chakravarty, P; Baruah, K K; Sarmah, B C (The Indian Journal of Animal Sciences, 2011)
A PGF2α analogue (5 ml) injection and ear implant (3 mg norgestomet, 5 mg Estradiol valerate) were used to synchronize oestrus in 2 different groups of Asom local cows, 5 in each group. The treated cows evinced oestrus after 99.00 ±3.00 and 29.80±0.01 h of hormone application in 2 groups, respectively, the respective response to treatment being 100 and 80% .Oestradiol 17–ß reached peak level in the 2 treated groups (145.66±7.89 and 99.00±1.99 pg/ml respectively) on the day of oestrus. On the contrary, the peak level of serum progesterone was recorded on day 14 and 16 of oestrous cycle in the 2 treated groups of animals respectively. The lowest serum progesterone level of 0.19±0.02 ng/ml and 0.24±0.13 ng/ml in PGF2α analogue and ear implant treated cows, respectively, was obtained on the day of induced oetrus. The present study indicated that while response in inducing synchronized oestrus was high, the variation in oestradiol 17–ß and progesterone profile in blood of Asom local cows with PGF2α analogue and ear implant application was similar to that in normal cycling cows.